Journey to health. Lesson 12, Managing your health. Part 3 - Dyer, Julia; Dallas TeleLearning (Firm) (Dallas, TX : Dallas County Community College District, 2003)
Managing Your Health examines the complexities of the modern health care delivery system in the U.S.
"Mind, body, spirit".
Title from resource description page (viewed May 31, 2019).
In English.
Keywords: Medical care -- United States; Health services accessibility; Health; Health planning; Health behavior; Health Services Accessibility; Health; Health Planning; Health Behavior; Services de santé -- Accessibilité.; Santé.; Santé publique -- Planification; Habitudes sanitaires; health; Health; Health behavior; Health planning; Health services accessibility; Medical care; United States; Instructional films; Instructional films; Films de formation